Multiethnic Genome-Wide Association Study of Subclinical Atherosclerosis in Individuals With Type 2 Diabetes. - Lu, Yingchang; Dimitrov, Latchezar; Chen, Shyh-Huei; Bielak, Lawrence F; Bis, Joshua C; Feitosa, Mary F; Lu, Lingyi; Kavousi, Maryam; Raffield, Laura M; Smith, Albert V; Wang, Lihua; Weiss, Stefan; et al. (Circ Genom Precis Med, 2021)
BACKGROUND: Coronary artery calcification (CAC) and carotid artery intima-media thickness (cIMT) are measures of subclinical atherosclerosis in asymptomatic individuals and strong risk factors for cardiovascular disease. Type 2 diabetes (T2D) is an independent cardiovascular disease risk factor that accelerates atherosclerosis. METHODS: We performed meta-analyses of genome-wide association studies in up to 2500 T2D individuals of European ancestry (EA) and 1590 T2D individuals of African ancestry with or without exclusion of prevalent cardiovascular disease, for CAC measured by cardiac computed tomography, and 3608 individuals of EA and 838 individuals of African ancestry with T2D for cIMT measured by ultrasonography within the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium. RESULTS: We replicated 2 loci (rs9369640 and rs9349379 near and rs10757278 near ) for CAC and one locus for cIMT (rs7412 and rs445925 near ) that were previously reported in the general EA populations. We identified one novel CAC locus (rs8000449 near at 13q13.3) at =2.0×10 in EA. No additional loci were identified with the meta-analyses of EA and African ancestry. The expression quantitative trait loci analysis with nearby expressed genes derived from arterial wall and metabolic tissues from the Genotype-Tissue Expression project pinpoints , encoding a matricellular protein involved in bone formation and bone matrix organization, as the potential candidate gene at this locus. In addition, we found significant associations (<3.1×10) for 3 previously reported coronary artery disease loci for these subclinical atherosclerotic phenotypes (rs2891168 near and rs11170820 near for CAC, and rs7412 near for cIMT). CONCLUSIONS: Our results provide potential biological mechanisms that could link CAC and cIMT to increased cardiovascular disease risk in individuals with T2D.